Gender differences in the psychological response to weight reduction in judoists - Yoshioka, Y.; Umeda, T.; Nakaji, S.; Kojima, A.; Tanabe, M.; Mochida. N.; Sugawara, K. (International Journal of Sport Nutrition and Exercise Metabolism, 2006)
We examined gender-related differences in the psychological response to weight reduction in 43 judoists. Twenty-two males and 8 females who required weight reduction [weight reduction (WR) group] (the average percentages of weight reduction observed for males and females were 3.4% and 4.9%, respectively), and 5 males and 8 females who did not require weight reduction (non-WR group). The POMS scores were measured before and after weight reduction. The TMD (total mood disturbance) score in POMS significantly increased after weight reduction only in WR group males. In the female WR group, the anger and depression scores decreased after weight reduction, and the pre-value of the TMD score in this group was relatively high. The psychological stress may be caused by anxiety engendered by the overall concept of weight reduction before actual weight reduction in females, whereas in males it may be caused by the actual weight reduction.